Bezpośrednie inwestycje zagraniczne w gospodarce regionu Dolnego Śląska - Zakrzewska-Półtorak, Alicja (Foreign Direct Investment in the Economy of Lower Silesia Region, 2006)
In this paper the author discusses selected trends of foreign direct investment (FDI) inflows and FDI inward stocks in Lower Silesia and points out some influences of FDI on Lower Silesia economy. Foreign direct investors were examined as: producers, exporters, tax payers and employers. The analysis included the period between 1999 and 2003. Special emphasis was given to the impact of FDI location on the development of the whole region, particular subregions and powiats (districts).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 172-182